Potret Persaudaraan Umat Beragama: Melacak Tradisi Keberagaman demi Terwujudnya Kerukunan Umat Beragama di Desa Tanon, Kecamatan Papar, Kabupaten Kediri: Portrait of Interfaith Brotherhood: Tracing the Tradition of Diversity to Achieve Religious Harmony in Tanon Village, Papar District, Kediri Regency - Syamsun Ni'am (Fenomena, 2008)
Amid globalization and the rise of religious-based conflicts in various parts of Indonesia, the concept of religious brotherhood has become critically important to re-examine. This study aims to understand the concept of religious harmony and to trace the religious traditions developed by the community of Tanon Village, Kediri, in achieving such harmony. Using a qualitative sociological-phenomenological approach, along with interviews, observation, and documentation, the research found that the Tanon community lives harmoniously despite high religious diversity, including Islam, Christianity, Hinduism, and Buddhism. Key factors supporting this harmony include the tradition of mutual cooperation, the dominance of moderate religious streams such as NU and GKJW, humanitarian-focused preaching, and close relationships among religious leaders. In conclusion, local social and cultural capital effectively maintains interfaith brotherhood. The study recommends strengthening interfaith dialogue and the government’s role as a facilitator to prevent religious-based conflicts. Di tengah arus globalisasi dan maraknya konflik bernuansa agama di berbagai wilayah Indonesia, pemahaman tentang persaudaraan umat beragama menjadi sangat genting untuk dikaji ulang. Penelitian ini bertujuan untuk memahami konsep kerukunan umat beragama serta menelusuri tradisi keberagamaan yang dikembangkan masyarakat Desa Tanon, Kediri, dalam mewujudkan kerukunan tersebut. Dengan menggunakan pendekatan kualitatif sosiologis-fenomenologis serta teknik wawancara, observasi, dan dokumentasi, penelitian ini menemukan bahwa masyarakat Tanon mampu hidup harmonis meskipun memiliki keragaman agama yang tinggi, termasuk Islam, Kristen, Hindu, dan Budha. Faktor utama yang mendorong kerukunan meliputi tradisi gotong-royong, dominasi aliran keagamaan moderat seperti NU dan GKJW, dakwah yang berfokus pada isu kemanusiaan, serta hubungan erat antar tokoh agama. Kesimpulannya, modal sosial dan kultural lokal terbukti efektif menjaga persaudaraan lintas iman. Penelitian ini merekomendasikan penguatan dialog antaragama dan peran pemerintah sebagai fasilitator untuk mencegah konflik berbasis agama.